A Longitudinal Study of a Chinese Man Presenting with Non-Fluent/Agrammatic Variant of Primary Progressive Aphasia - Liu, Xiaoyan; He, Fangping; Chen, Zhongqin; Liu, Ping; Peng, Guoping (Frontiers in Neurology, 2018)
Primary progressive aphasia (PPA) is a neurodegenerative disease characterized by declining language ability. However, the difficulty in defining the central clinical features in its earliest stage and establishing the dynamics of its progression has led to controversy. We report a 71-year-old man with Han language suffering from non-fluent/agrammatic variant of PPA but presenting as typical Alzheimer’s disease (AD) and confused with logopenic variant of PPA in its early stage, longitudinally describing his clinical characteristics, neuroanatomical basis, and genetic associations, and exploring the underlying pathology. This case highlights a longitudinal data for reliably discriminating among AD and PPA variants and helps to deepen our understanding of Han language non-fluent/agrammatic variant of PPA.